Preparation method of insulating ceramic material
Through the porous structure and liquid phase blending technology of silicon-based porous materials, the fragility problem of alumina ceramic materials is solved, the toughness and density of the ceramics are improved, the service life is extended and the bubble content is reduced.
Patent Information
- Application Number
- CN202411631602.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The fragility of alumina ceramic materials makes the service life difficult to estimate and increase maintenance costs.
Porous structure is formed by silicon-based porous materials, and a viscous liquid is formed by low-temperature ultrasonic treatment of ethyl cellulose, bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane. After spray deposition, it is used with isopropyl Aluminum blending of alcohol and aluminum alcohol blending technology forms a frame structure that is transparent inside and outside through spray dispersion and liquid phase blending technology, improving the internal toughness of the ceramic.
It effectively improves the brittleness of alumina ceramic materials, improves the density and toughness of the ceramics, extends the service life, reduces the bubble content, and reduces the difficulty of subsequent processing.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a method for preparing an insulating ceramic material. Background Art
[0002] With the rapid development of the national economy, the scale of the power grid is also growing. At the same time, people's requirements for the reliability of power supply are getting higher and higher, which requires all equipment in the power grid to operate stably and reliably for a long time. Alumina, as an inorganic material with high melting point and high hardness, has excellent thermal conductivity and good electrical insulation, making it the preferred insulating ceramic material. In addition, the advantages of alumina such as wide sources, low prices and good chemical stability have greatly increased the scope of application of alumina. However, alumina ceramics are brittle and prone to breakage, internal cracks and other problems, making it difficult to predict their service life and greatly increasing maintenance costs. Summary of the invention
[0003] In response to the problems in the prior art, the present invention provides a method for preparing an insulating ceramic material, which solves the brittleness problem of existing alumina ceramic materials. A porous structure is formed by using silicon-based porous materials, which not only provides a silicon hydroxyl active system to enhance the active connection and density with alumina, but also the porous structure can form a framework structure that is transparent inside and outside, thereby improving the internal toughness of the ceramic, thereby achieving the purpose of improving brittleness.
[0004] In order to achieve the above technical objectives, the technical solution of the present invention is: A method for preparing an insulating ceramic material comprises the following steps: Step 1, adding ethyl cellulose to ether and stirring evenly, then adding bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane and performing low temperature ultrasonication for 20-30 minutes, and forming a viscous liquid after standing, wherein the concentration of the ethyl cellulose in the ether is 400-600 g / L, the stirring speed for even stirring is 100-400 r / min, the molar ratio of the bis(3-chloropropyl)dichlorosilane to the 3-chloropropyltrichlorosilane is 1:2-3, and the molar ratio of the bis(3-chloropropyl)dichlorosilane to the ethyl cellulose is 1:2-3. The mass ratio is 1:1.5-3, the temperature of the low-temperature ultrasound is 10-15°C, the ultrasonic frequency is 60-80kHz; the temperature of the static state is 20-30°C; this step utilizes the solubility of ethyl cellulose, bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane in ether to form a liquid phase dispersion, and the low-temperature ultrasound method improves the homogenization effect of the three, and the volatile ether forms a slow removal of the solvent, thereby obtaining a viscous liquid with ethyl cellulose as a dispersant and a binder; Step 2: ultrasonically treat the viscous liquid for 20-30 minutes and then spray it into distilled water, and deposit it at low temperature for 10-20 minutes, then heat it up and stir it for 0.5-1h, and filter and wash it to obtain silicon-based porous particles. The temperature of the ultrasonic treatment is 4-10°C, the ultrasonic frequency is 60-80kHz, the spraying speed is 3-5mL / min, and the area is 10-30cm 2 , the temperature of the distilled water is 40-50°C; the temperature of the low-temperature deposition is 10-20°C, the temperature of the heating and stirring is 70-80°C, and the stirring speed is 300-600r / min; the washing uses ethanol; this step uses ultrasound to homogenize and disperse the viscous liquid to solve the problem of solute deposition, and uses a spray method to homogenize the viscous liquid on the distilled water. At this time, the temperature of the distilled water is higher than the boiling point of ether, which can quickly remove the ether and ensure that the solute particles enter the distilled water; the solute particles contain bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane, which can form a hydrolysis reaction with the water molecules in the distilled water, and in situ condense the silicon hydroxyl groups during heating and stirring; ethyl cellulose has good stability in water, will not dissolve, and has an excellent barrier effect, thereby obtaining a stable porous structure; during the washing process, ethyl cellulose can be dissolved in ethanol to achieve rapid separation and expose the silicon-oxygen porous structure, that is, the silicon-based porous particles; Step 3, adding aluminum isopropoxide to ethanol and mixing evenly, then adding silicon-based porous particles and stirring evenly, then sealing and stirring for 1-3h, filtering while hot and cooling to obtain silicon-aluminum composite particles, the concentration of aluminum isopropoxide in ethanol is 500-700g / L, the mass ratio of the silicon-based porous particles to aluminum isopropoxide is 1:3-5, the stirring speed for uniform stirring is 400-500r / min, and the temperature is 80-90°C; the temperature of the sealed stirring is 120-130°C, the stirring speed is 300-500r / min, and the temperature of the hot filtration is 1 18-120°C; This step utilizes the solubility of aluminum isopropoxide in ethanol to form a homogeneous dispersion, and gradually removes ethanol when adding silicon-based porous particles to form a mixture of aluminum isopropoxide and silicon-based porous particles. During sealed stirring, the aluminum isopropoxide liquefies to form a liquid and enters the silicon-based porous particles. Combined with the viscosity of the aluminum isopropoxide itself and the mass of the aluminum isopropoxide being much greater than that of the silicon-based porous particles, the aluminum isopropoxide liquid can fill the pores in the silicon-based porous particles. During hot filtration and cooling treatment, the aluminum isopropoxide in the silicon-based porous particles solidifies and achieves a filling effect; Step 4, adding aluminum isopropoxide and trichloromethylsilane to ether and stirring evenly, then performing reduced pressure distillation to obtain a premix, and finally stirring the silicon-oxygen composite particles evenly to obtain a mixture, wherein the mass ratio of aluminum isopropoxide to trichloromethylsilane is 10-15:1, the mass ratio of aluminum isopropoxide to ether is 1:4-5, the stirring speed for uniform stirring is 100-200r / min, the pressure of the reduced pressure distillation is 80-90% of the atmospheric pressure, and the temperature is 25-30°C; the mass ratio of the silicon-oxygen composite particles to aluminum isopropoxide is 1:3-5, and the stirring speed for uniform stirring is 300-500r / min; in this step, aluminum isopropoxide and trichloromethylsilane are formed into a good homogeneous mixture by liquid phase mixing, and the ether is taken out by reduced pressure distillation, and then the silicon-oxygen composite particles are added to achieve the effect of blending; Step 5, placing the mixture in a mold and letting it stand for 3-5 hours, then extruding and heating for 4-6 hours, and sintering to obtain an insulating ceramic material, wherein the atmosphere of the standing state is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 7-8:1, and the temperature is 30-40°C; the pressure of the extrusion heating is 0.4-0.6MPa, the temperature is 200-230°C, the temperature of the sintering is 1400-1500°C, and the time is 1-3h; this step uses the standing state to form distilled water in the mixed state with the water vapor in the standing state. The penetration of methyltrichlorosilane and aluminum isopropoxide into the material promotes the in-situ hydrolysis of methyltrichlorosilane and aluminum isopropoxide, and forms silanol and aluminum hydroxyl reactions during the extrusion and heating process to achieve good dense connectivity. At the same time, the silanol activity in the silicon-based porous material plays a good connectivity role, thereby improving the connection density and toughness in the condensation polymer. Moreover, the silicon-based porous material itself has porosity, which ensures the synchronous hydrolysis of aluminum isopropoxide and condensation of aluminum hydroxyl inside and outside, achieving the effect of internal and external integration; therefore, the silicon-based porous material plays a supporting and connecting role, which improves the toughness of the insulating ceramic material.
[0005] It can be seen from the above description that the present invention has the following advantages: 1. The present invention solves the brittleness problem of existing alumina ceramic materials and utilizes silicon-based porous materials to form a porous structure, which not only provides a silanol active system to enhance the active connection and compactness with alumina, but also the porous structure can form a framework structure that is transparent inside and outside, thereby enhancing the internal toughness of the ceramic, thereby achieving the purpose of improving brittleness.
[0006] 2. The present invention adopts a liquid phase blending system of aluminum isopropoxide and silicon-based porous particles to ensure that the aluminum isopropoxide enters the silicon-based porous particles, which can reduce the bubbles in the silicon-based porous particles in subsequent processing, reduce the difficulty of subsequent processing, and also reduce the bubbles in the ceramic material.
[0007] 3. The present invention adopts spray dispersion and the insolubility of ethyl cellulose, which can form in-situ hydrolysis and polycondensation while maintaining the particle state in distilled water to form a stable porous structure of the silicon-oxygen framework. DETAILED DESCRIPTION
[0008] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.
[0009] Example 1 A method for preparing an insulating ceramic material comprises the following steps: Step 1, adding ethyl cellulose to diethyl ether and stirring evenly, then adding bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane and performing low-temperature ultrasound for 20 minutes, and forming a viscous liquid after standing, wherein the concentration of the ethyl cellulose in the diethyl ether is 400 g / L, the stirring speed for uniform stirring is 100 r / min, the molar ratio of the bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane is 1:2, the mass ratio of 3-chloropropyltrichlorosilane to ethyl cellulose is 1:1.5, the temperature of the low-temperature ultrasound is 10°C, the ultrasound frequency is 60 kHz; the standing temperature is 20°C; Step 2: The viscous liquid is ultrasonicated for 20 minutes and then sprayed into distilled water, and low-temperature deposited for 10 minutes, and then heated and stirred for 0.5 hours. After filtering and washing, silicon-based porous particles are obtained. The temperature of the ultrasonication is 4°C, the ultrasonic frequency is 60kHz, the spraying speed is 3mL / min, and the area is 10cm 2 , the temperature of distilled water is 40°C; the temperature of the low temperature deposition is 10°C, the temperature of the heating and stirring is 70°C, and the stirring speed is 300r / min; the washing adopts ethanol; Step 3, adding aluminum isopropoxide to ethanol and mixing evenly, then adding silicon-based porous particles and stirring evenly, then sealing and stirring for 1 hour, filtering while hot and cooling to obtain silicon-aluminum composite particles, the concentration of aluminum isopropoxide in ethanol is 500g / L, the mass ratio of the silicon-based porous particles to aluminum isopropoxide is 1:3, the stirring speed for uniform stirring is 400r / min, and the temperature is 80°C; the temperature of the sealed stirring is 120°C, the stirring speed is 300r / min, and the temperature of the hot filtration is 118°C; Step 4, adding aluminum isopropoxide and trichloromethylsilane to ether and stirring evenly, then performing reduced pressure distillation to obtain a premix, and finally stirring the silicon-oxygen composite particles evenly to obtain a mixture, wherein the mass ratio of aluminum isopropoxide to trichloromethylsilane is 10:1, the mass ratio of aluminum isopropoxide to ether is 1:4, the stirring speed for even stirring is 100 r / min, the pressure of the reduced pressure distillation is 80% of the atmospheric pressure, and the temperature is 25° C.; the mass ratio of the silicon-oxygen composite particles to aluminum isopropoxide is 1:3, and the stirring speed for even stirring is 300 r / min; Step 5, placing the mixture into a mold and letting it stand for 3-5 hours, then extruding and heating for 4 hours, and sintering to obtain an insulating ceramic material, wherein the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 7:1, and the temperature is 30°C; the extrusion heating pressure is 0.4MPa, the temperature is 200°C, the sintering temperature is 1400°C, and the time is 1h.
[0010] Example 2 A method for preparing an insulating ceramic material comprises the following steps: Step 1, adding ethyl cellulose to diethyl ether and stirring evenly, then adding bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane and performing low-temperature ultrasound for 30 minutes, and forming a viscous liquid after standing, wherein the concentration of the ethyl cellulose in the diethyl ether is 600 g / L, the stirring speed for uniform stirring is 400 r / min, the molar ratio of the bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane is 1:3, the mass ratio of 3-chloropropyltrichlorosilane to ethyl cellulose is 1:3, the temperature of the low-temperature ultrasound is 15°C, the ultrasound frequency is 80 kHz; the standing temperature is 30°C; Step 2: The viscous liquid is ultrasonically treated for 30 minutes and then sprayed into distilled water, and low-temperature deposited for 20 minutes, and then heated and stirred for 1 hour, and then filtered and washed to obtain silicon-based porous particles. The ultrasonic temperature is 10°C, the ultrasonic frequency is 80kHz, the spray speed is 5mL / min, and the area is 30cm 2 , the temperature of distilled water is 50°C; the temperature of the low temperature deposition is 20°C, the temperature of the heating and stirring is 80°C, and the stirring speed is 600r / min; the washing adopts ethanol; Step 3, adding aluminum isopropoxide to ethanol and mixing evenly, then adding silicon-based porous particles and stirring evenly, then sealing and stirring for 3 hours, filtering while hot and cooling to obtain silicon-aluminum composite particles, the concentration of aluminum isopropoxide in ethanol is 700g / L, the mass ratio of the silicon-based porous particles to aluminum isopropoxide is 1:5, the stirring speed for uniform stirring is 500r / min, and the temperature is 90°C; the temperature of the sealed stirring is 130°C, the stirring speed is 500r / min, and the temperature of the hot filtration is 120°C; Step 4, adding aluminum isopropoxide and trichloromethylsilane to ether and stirring evenly, then performing reduced pressure distillation to obtain a premix, and finally stirring the silicon-oxygen composite particles evenly to obtain a mixture, wherein the mass ratio of aluminum isopropoxide to trichloromethylsilane is 15:1, the mass ratio of aluminum isopropoxide to ether is 1:5, the stirring speed for even stirring is 200 r / min, the pressure of the reduced pressure distillation is 90% of the atmospheric pressure, and the temperature is 30° C.; the mass ratio of the silicon-oxygen composite particles to aluminum isopropoxide is 1:5, and the stirring speed for even stirring is 500 r / min; Step 5, placing the mixture into a mold and letting it stand for 5 hours, then extruding and heating it for 6 hours, and sintering it to obtain an insulating ceramic material. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the temperature is 40°C; the extrusion heating pressure is 0.6MPa, the temperature is 230°C, the sintering temperature is 1500°C, and the time is 3 hours.
[0011] Example 3 A method for preparing an insulating ceramic material comprises the following steps: Step 1, adding ethyl cellulose to diethyl ether and stirring evenly, then adding bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane and performing low-temperature ultrasound for 25 minutes, and forming a viscous liquid after standing, wherein the concentration of the ethyl cellulose in the diethyl ether is 500 g / L, the stirring speed for uniform stirring is 300 r / min, the molar ratio of the bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane is 1:3, the mass ratio of 3-chloropropyltrichlorosilane to ethyl cellulose is 1:2, the temperature of the low-temperature ultrasound is 13°C, the ultrasound frequency is 70 kHz; the standing temperature is 25°C; Step 2: The viscous liquid is ultrasonically treated for 25 minutes and then sprayed into distilled water, and low-temperature deposited for 15 minutes, and then heated and stirred for 1 hour. After filtering and washing, silicon-based porous particles are obtained. The temperature of the ultrasonic treatment is 8°C, the ultrasonic frequency is 70kHz, the spraying speed is 4mL / min, and the area is 20cm 2 , the temperature of the distilled water is 45°C; the temperature of the low temperature deposition is 15°C, the temperature of the heating and stirring is 75°C, and the stirring speed is 500r / min; the washing adopts ethanol; Step 3, adding aluminum isopropoxide to ethanol and mixing evenly, then adding silicon-based porous particles and stirring evenly, then sealing and stirring for 2 hours, filtering while hot and cooling to obtain silicon-aluminum composite particles, the concentration of aluminum isopropoxide in ethanol is 600g / L, the mass ratio of the silicon-based porous particles to aluminum isopropoxide is 1:4, the stirring speed for uniform stirring is 450r / min, and the temperature is 85°C; the temperature of the sealed stirring is 125°C, the stirring speed is 400r / min, and the temperature of the hot filtration is 119°C; Step 4, adding aluminum isopropoxide and trichloromethylsilane to ether and stirring evenly, then performing reduced pressure distillation to obtain a premix, and finally stirring the silicon-oxygen composite particles evenly to obtain a mixture, wherein the mass ratio of aluminum isopropoxide to trichloromethylsilane is 13:1, the mass ratio of aluminum isopropoxide to ether is 1:5, the stirring speed for even stirring is 150 r / min, the pressure of the reduced pressure distillation is 85% of the atmospheric pressure, and the temperature is 28° C.; the mass ratio of the silicon-oxygen composite particles to aluminum isopropoxide is 1:4, and the stirring speed for even stirring is 400 r / min; Step 5, placing the mixture into a mold and letting it stand for 4 hours, then extruding and heating it for 5 hours, and sintering it to obtain an insulating ceramic material. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the temperature is 35°C; the extrusion heating pressure is 0.5MPa, the temperature is 220°C, the sintering temperature is 1450°C, and the time is 2h.
[0012] Comparative Example 1 A method for preparing an insulating ceramic material comprises the following steps: Step 1, adding aluminum isopropoxide and trichloromethylsilane to diethyl ether and stirring evenly, and then distilling under reduced pressure to obtain a mixture, wherein the mass ratio of aluminum isopropoxide to trichloromethylsilane is 13:1, the mass ratio of aluminum isopropoxide to diethyl ether is 1:5, the stirring speed for uniform stirring is 150 r / min, the pressure of the reduced pressure distillation is 85% of the atmospheric pressure, and the temperature is 28° C.; Step 2, placing the mixture into a mold and letting it stand for 4 hours, then extruding and heating it for 5 hours, and sintering it to obtain an insulating ceramic material. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the temperature is 35°C; the extrusion heating pressure is 0.5MPa, the temperature is 220°C, the sintering temperature is 1450°C, and the time is 2h.
[0013] Comparative Example 2 A method for preparing an insulating ceramic material comprises the following steps: Step 1, adding aluminum isopropoxide and nano-silicon dioxide to ether and stirring evenly, and then distilling under reduced pressure to obtain a mixture, wherein the mass ratio of aluminum isopropoxide to nano-silicon dioxide is 13:1, the mass ratio of aluminum isopropoxide to ether is 1:5, the stirring speed for uniform stirring is 150 r / min, the pressure of the reduced pressure distillation is 85% of the atmospheric pressure, and the temperature is 28° C.; Step 2, placing the mixture into a mold and letting it stand for 4 hours, then extruding and heating it for 5 hours, and sintering it to obtain an insulating ceramic material. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, and the temperature is 35°C; the extrusion heating pressure is 0.5MPa, the temperature is 220°C, the sintering temperature is 1450°C, and the time is 2h.
[0014] The products of Examples 1-3 and the samples of Comparative Examples 1-3 were used as test samples to conduct performance tests, and the results are as follows:
[0015] Through the above data comparison, this technical solution uses silicon-based porous particles as additives, which can not only effectively improve the toughness and mechanical embedding end of insulating ceramics, but also cooperate with silicon oxide precursors to form penetration and connection, effectively improving the density and stability of insulating materials, and greatly extending the service life of the product.
[0016] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A method for preparing an insulating ceramic material, characterized in that: The steps include: Step 1, adding ethyl cellulose to ether and stirring evenly, then adding bis(3-chloropropyl)dichlorosilane and 3-chloropropyltrichlorosilane and performing low temperature ultrasonic treatment for 20-30 minutes, and forming a viscous liquid after standing; Step 2, after ultrasonicating the viscous liquid for 20-30 minutes, spraying it into distilled water, and depositing it at low temperature for 10-20 minutes, then heating it and stirring it for 0.5-1 hour, and filtering and washing it to obtain silicon-based porous particles; Step 3, adding aluminum isopropoxide to ethanol and mixing evenly, then adding silicon-based porous particles and stirring evenly, then sealing and stirring for 1-3 hours, filtering while hot and cooling to obtain silicon-aluminum composite particles; Step 4, adding aluminum isopropoxide and trichloromethylsilane to ether and stirring evenly, then distilling under reduced pressure to obtain a premix, and finally stirring the silicon-oxygen composite particles evenly to obtain a mixture; Step 5, placing the mixture into a mold and letting it stand for 3-5 hours, then extruding and heating it for 4-6 hours, and sintering it to obtain an insulating ceramic material.
2. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The concentration of ethyl cellulose in ether in step 1 is 400-600 g / L, and the stirring speed for uniform stirring is 100-400 r / min.
3. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The molar ratio of bis(3-chloropropyl)dichlorosilane to 3-chloropropyltrichlorosilane in step 1 is 1:2-3, the mass ratio of 3-chloropropyltrichlorosilane to ethyl cellulose is 1:1.5-3, the temperature of the low-temperature ultrasound is 10-15°C, the ultrasonic frequency is 60-80kHz; and the standing temperature is 20-30°C.
4. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The ultrasonic temperature in step 2 is 4-10°C, the ultrasonic frequency is 60-80kHz, the spray speed is 3-5mL / min, and the area is 10-30cm 2 , the temperature of distilled water is 40-50℃.
5. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The temperature of the low-temperature deposition in step 2 is 10-20° C., the temperature of the heating and stirring is 70-80° C., and the stirring speed is 300-600 r / min; and ethanol is used for washing.
6. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The concentration of aluminum isopropoxide in ethanol in step 3 is 500-700 g / L, the mass ratio of the silicon-based porous particles to aluminum isopropoxide is 1:3-5, the stirring speed for uniform stirring is 400-500 r / min, and the temperature is 80-90° C.; the temperature of the sealed stirring is 120-130° C., the stirring speed is 300-500 r / min, and the temperature of the hot filtration is 118-120° C.
7. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The mass ratio of aluminum isopropoxide to trichloromethylsilane in step 4 is 10-15:1, the mass ratio of aluminum isopropoxide to ether is 1:4-5, the stirring speed for uniform stirring is 100-200 r / min, the pressure of the reduced pressure distillation is 80-90% of the atmospheric pressure, and the temperature is 25-30°C.
8. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The mass ratio of the silicon-oxygen composite particles to aluminum isopropoxide in step 4 is 1:3-5, and the stirring speed for uniform stirring is 300-500 r / min.
9. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The static atmosphere in step 5 is a mixed atmosphere of nitrogen and water vapor, wherein the volume ratio of nitrogen to water vapor is 7-8:1, and the temperature is 30-40°C.
10. The method for preparing an insulating ceramic material according to claim 1, characterized in that: The pressure of the extrusion heating in step 5 is 0.4-0.6 MPa, the temperature is 200-230° C., the temperature of the sintering is 1400-1500° C., and the time is 1-3 h.
Citation Information
Patent Citations
Preparation method of quartz ceramic roller
CN113896516A
Composite porous ceramic reinforced aluminum alloy material
CN116178024A
Preparation method of composite insulating material
CN117720814A
Antiskid noise-reducing asphalt concrete and preparation method thereof
CN118344055A
Infrared absorption material, method for fabricating the same, and thermal isolation structure employing the same
US20150030802A1
